2023
DOI: 10.3390/molecules28062764
|View full text |Cite
|
Sign up to set email alerts
|

Donor-π-Acceptor-Type Fluorinated Tolane Containing a Semifluoroalkoxy Chain as a Condensed-Phase Luminophore

Abstract: Photoluminescent liquid-crystalline (PLLC) molecules, which can easily tune the PL behavior through the crystal (Cry)–LC phase transition, have attracted significant attention. Previously, we have demonstrated that the incorporation of a semifluoroalkoxy chain into π-conjugated mesogen is a promising approach for developing PLLC molecules with PL and SmA LC characteristics. We focused on the LC and PL characteristics of the molecules induced by the semifluoroalkoxy chain and fluorinated tolanes in the condense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The fluorinated tolanecarboxylate 18-F with a semifluoroalkoxy-type flexible chain showed PL even in the N phase, whereas λ PL was blue-shifted approximately 20 nm to exhibit a light-blue PL (Figure 24a). [29] The fluorinated tolane dimer 19-F 10 connected by a decylene chain and 20-F 5 connected by a pentylene chain also caused a slight blue shift of λ PL through phase transition between Cry and N or SmA LC phases (Figures 24b and 24c). [32,33] Similar to 18-F, it was found that PL intensity of 19-F 10 and 20-F 5 caused a significant decrease in the molecular aggregates of LC phase.…”
Section: Pl Behavior In the Lc Phasementioning
confidence: 96%
See 1 more Smart Citation
“…The fluorinated tolanecarboxylate 18-F with a semifluoroalkoxy-type flexible chain showed PL even in the N phase, whereas λ PL was blue-shifted approximately 20 nm to exhibit a light-blue PL (Figure 24a). [29] The fluorinated tolane dimer 19-F 10 connected by a decylene chain and 20-F 5 connected by a pentylene chain also caused a slight blue shift of λ PL through phase transition between Cry and N or SmA LC phases (Figures 24b and 24c). [32,33] Similar to 18-F, it was found that PL intensity of 19-F 10 and 20-F 5 caused a significant decrease in the molecular aggregates of LC phase.…”
Section: Pl Behavior In the Lc Phasementioning
confidence: 96%
“…[28] Thus, we investigated 17-F with a CN group and 18-F with an COOEt group (Figure 13). [29] We initially investigated the phase transition behavior 15-F and 16-F having a decyloxy chain, and 17-F and 18-F having a nonafluorodecyloxy chain. [29] Contrary to our expectations, unfortunately, both fluorinated tolanes with a decyloxy chain (15-F and 16-F) exhibited only phase-transitions between the crystalline (Cry) and the isotropic (Iso) phases during both the 2 nd heating and cooling processes (Figure 13b, Table 4).…”
Section: Fluorinated Tolane-based Pllc Moleculesmentioning
confidence: 99%
“…1 H nuclear magnetic resonance (NMR) (400 MHz) and 13 C NMR (100 MHz) spectra were acquired using an AVANCE III 400 NMR spectrometer (Bruker, Rheinstetten, Germany) in chloroform-d (CDCl 3 ) solution, and chemical shifts are reported in parts per million (ppm) based on the residual protons or carbon in the NMR solvent. 19 F NMR (376 MHz) spectra were acquired using an AVANCE III 400 NMR spectrometer (Bruker, Rheinstetten, Germany) in CDCl 3 solution with C 6 F 6 (δ F = −163 ppm) as an internal stan-dard. Infrared (IR) spectra were recorded using the KBr method on a FTIR-4100 type A spectrometer (JASCO, Tokyo, Japan).…”
Section: Generalmentioning
confidence: 99%
“…Recently, our group explored molecules that have both LC and photoluminescence properties and successfully developed donor-π-acceptor (D-π-A)-type tolane derivatives that have an electron-donating alkoxy group and an electron-withdrawing cyano group at their molecular ends [17][18][19]. Among our achievements, the D-π-A-type tolane bearing a decyloxy (C10H21O) chain formed a nematic (N) LC phase as a mesophase (Figure 1a) [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation